2017
DOI: 10.3892/mmr.2017.6771
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of type II collagen, matrix metalloproteinase-13 and cell proliferation by interleukin-1β is mediated by curcumin via inhibition of NF-κB signaling in rat chondrocytes

Abstract: Curcumin possesses strong anti-inflammatory, anti-rheumatoid and anti-oxidative activities, and has the potential to inhibit nuclear factor-κB (NF-κB) signaling. Cartilage damage in osteoarthritis (OA) is largely mediated by interleukin-1β (IL-1β) via activation of various transcription factors, including NF-κB and activator protein-1. The aim of the present study was to determine whether IL-1β induces matrix metalloproteinase-13 (MMP-13) expression and inhibits type II collagen expression, as well as to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 34 publications
4
47
1
1
Order By: Relevance
“…Wang et al . demonstrate that curcumin can treat osteoarthritis by inhibiting NF‐κB signaling. Clutterbuck et al .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . demonstrate that curcumin can treat osteoarthritis by inhibiting NF‐κB signaling. Clutterbuck et al .…”
Section: Discussionmentioning
confidence: 99%
“…Its therapeutic potential covers diseases such as cancer, Alzheimer's disease, osteoporosis, inflammatory bowel disease, depression, arthritis, diabetes, vitiligo, endometriosis, and several others. Figure 2 shows some effects of curcumin [5, [28][29][30].…”
Section: Curcuma Longamentioning
confidence: 99%
“…Consequently, it inhibits the expression of pro-apoptotic genes in chondrocytes (caspase-3) and the formation of inflammatory mediators [18]. Thus, it is responsible for the downregulation of lipoxygenases, COX-2, phospholipase A2, prostaglandin E2 (PGE2), IL-1β, IL-6, and IL-8 [19,30]. Wherefore, curcumin blocks the signaling by NF-kB, leading to the inhibition of this factor resulting in the decrease of the degradation of collagen.…”
Section: The Potential Effects Of Curcuma Longamentioning
confidence: 99%
See 1 more Smart Citation
“…The biological activities of turmeric include antiproliferative, antiinflammatory, and antioxidation activities (Menon & Sudheer, ). One study showed that curcumin from turmeric downregulated MMP‐13 expression while upregulating type II collagen expression, through its inhibition of NF‐κB activation (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%